Geldwertsicherung im internationalen Goldstandard und in einer Währungsunion von Staaten mit Papierstandard aus institutionenökonomischer Sicht1. (17th July 2013) - Richter, Rudolf
Abstract: Economists have a hard time to predict macro‐institutional developments. Missing are predictions based on tried and tested hypotheses. Why not apply proved micro‐institutional hypotheses to macro‐institutional problems like the European Economic Union (EMU)? We try to do that. The international gold standard serves only as counterexample. We discuss the sustainability of EMU (= stability of the euro) using a number of well‐tested hypotheses of institutional economics – up to the explanation of firm mergers. Yet different from business mergers, to endure, mergers of states must become self‐enforcing entities, which requires ideological (cultural) integration of its citizens.